Using Low-Density Parity-Check Codes to Reduce the Effect of Laser Line width For Optical Communication - Fyath, R. S.; Darweesh, Hussam A. (Nahrain University College of Engineering Journal, 2011)
The performance of coherent optical communication systems is degraded significantly by the phase noise of the semiconductor lasers. The phase noise is induced by spontaneous emission in the laser cavity and yields broadening in the laser linewidth. This paper addresses the application of the Low-DensityParity-Check (LDPC) codes as Forward Error Correcting (FEC) codes to relax the laser linewidth requirement. These codes are applied to three types of heterodyne optical receivers (BPSK, DPSK and QPSK) operating with finite laser linewidths